The late Oligocene flora from the Río Leona Formation, Argentinian Patagonia - Cesari, Silvia Nelida (2015)
A late Oligocene plant macrofossil assemblage is described from the Río Leona Formation, Argentinian Patagonia. This includes a fern, “Blechnum” turbioense Frenguelli, one species of conifer, and sixteen angiosperm taxa. Rosaceae, Myrtaceae, Proteaceae, Lauraceae, Anacardiaceae and Typhaceae are represented by one species in each family. Five species are considered to be members of the Fabales. Three leaf taxa together with Carpolithus seeds are placed in the Nothofagaceae. Palynomorphs and permineralized woods complete the floral record of the Río Leona Formation, which is considered early late Oligocene based on radiometric dating and palynofloras.